2020
DOI: 10.1101/2020.10.04.20206094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of the knowledge, attitudes, and practices of physicians, health workers, and the general population about Coronavirus disease 2019 (COVID-19)

Abstract: Background: Understanding people, physicians, and healthcare workers' knowledge, attitude, and practices (KAPs) can help to achieve the outcomes of planned behavior. The aim of this study was to investigate and synthesize the current evidence on KAPs regarding COVID-19. Methods: We conducted a systematic search on PubMed/LitCovid, Scopus, and Web of Sciences databases for papers in the English language only, up to 1 Jul 2020. We used the Joanna Briggs Institute (JBI) checklist developed for cross-sectional stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…In contrary to our results, a low level of practices was reported in a systematic review study. This difference may be due to the good performance of the officials in Hormozgan province in controlling, preventing, providing appropriate supplies (such as masks and disinfectants), and training programs (Saadatjoo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In contrary to our results, a low level of practices was reported in a systematic review study. This difference may be due to the good performance of the officials in Hormozgan province in controlling, preventing, providing appropriate supplies (such as masks and disinfectants), and training programs (Saadatjoo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“… 65 With the global spread of COVID-19, awareness has increased among the general public and knowledge regarding the COVID-19 pandemic has reached a relatively high level. 66 However, there is still room for effort in driving COVID-19 related knowledge to preventive behavior changes.…”
Section: Discussionmentioning
confidence: 99%
“…A total of five hundred and sixty four people participated in this cross-sectional study and showed a good sense of knowledge, attitude and practices towards the ongoing Coronavirus pandemic as concluded in a previous study by Saadatjoo S. et al [8]. This survey was taken by both male and female participants (see Table 1) in which the percentage of male participants (57.6%) comprised the majority and we found no sex differences about Knowledge, Attitude and Practices towards Coronavirus as both males and females were found to be well-versed with Knowledge, Attitude and Practices towards Coronavirus as previously observed in a crosssectional survey conducted by Okello G. et al [9] on Knowledge, Attitude and Practices about Coronavirus in Uganda.…”
Section: Resultsmentioning
confidence: 61%